Silicon carbide grinding sheet and method for nondestructive testing of grinding damage layer of grinding sheet

The non-destructive testing of the silicon carbide abrasive sheets is solved through Raman spectroscopy, which solves the problem of residual wear and damage layer, and optimizes the grinding and polishing processes, improves the quality and yield of silicon carbide devices, and simplifies the process flow.

CN119141432AActive Publication Date: 2024-12-17SICC CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310713252.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove the abrasive damage layer during the grinding process of silicon carbide abrasive sheets, resulting in the residual of the abrasive damage layer affecting the surface convexity and physical properties parameters of the silicon carbide substrate. The traditional KOH corrosion method is a destructive method and cannot be used in real time. Detect the removal of the wear-damaged layer, resulting in rework and waste of resources.

Method used

Raman spectroscopy technology is used to conduct non-destructive testing on the surface of the grinding sheet. The size and distribution of the wear damage layer are judged by measuring the stress distribution map, guiding the improvement of the grinding and polishing process, reducing the introduction of wear damage stress and optimizing subsequent processes.

Benefits of technology

Non-destructive testing of the abrasive damaged layer of the abrasive sheet is realized, processing processes are saved, resource waste is avoided, yield and performance of silicon carbide devices are improved, and process flow is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119141432A_ABST
    Figure CN119141432A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon carbide grinding sheet and a method for nondestructive testing of a grinding damage layer of the grinding sheet, and belongs to the technical field of silicon carbide production and processing. The detection method comprises the following steps: (1) extending from the surface of the grinding sheet inwards by 20-30 [mu] m so as to carry out Raman test on the surface layer of the grinding sheet to obtain a stress distribution diagram of the surface layer of the grinding sheet; (2) the stress distribution diagram is divided into a first square area and a second square area with the side length being 100 micrometers, the first square area is the area with the stress value absolute value larger than 35 MPa, the second square area is the area with the stress value absolute value smaller than or equal to 30 MPa, and the stress distribution diagram is obtained according to the proportion of the first square area; and judging whether the grinding damage layer of the grinding sheet is completely removed or not. Nondestructive testing can be directly carried out on the grinding sheet through Raman, so that the size of a grinding damage layer of the grinding sheet is reflected, and the method can be directly used for guiding improvement of a grinding process and a polishing process according to a detection result.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a silicon carbide grinding sheet and a method for grinding a damaged layer of the grinding sheet for non-destructive testing, and belongs to the technical field of silicon carbide production and processing. Background Art

[0002] Silicon carbide crystals are cut and separated by multi-wire cutting to obtain silicon carbide wafer substrates. However, since there are a large number of line marks and cutting damage layers on the surface after cutting, it is necessary to grind and remove the cutting damage layers to obtain grinding sheets. During the grinding process, the abrasive and the silicon carbide substrate are pressed and rubbed in hard contact with the grinding disk to achieve the purpose of thickening and removing the cutting damage layer. However, the grinding damage layer will inevitably be introduced again in this process, so the grinding sheet generally needs to be polished to further remove the grinding damage layer of the grinding sheet.

[0003] The introduction of the grinding damage layer will affect the surface roughness and other physical parameters of the silicon carbide substrate. At present, the KOH corrosion method is often used to verify the existence of the chip grinding damage layer. The chip is corroded by hot KOH solution to confirm the damage of the grinding surface after polishing. In addition to the normal dislocation corrosion pits, if there are a large number of dense water droplet-shaped corrosion pits, it means that the grinding damage layer still remains after polishing. If only dislocation corrosion pits can be seen under an optical microscope after corrosion, and other areas are flat and smooth, it means that the grinding damage layer has been basically removed. Since the surface of the grinding sheet is in a non-mirror state and no defects can be seen by corrosion, this method is only performed on the polished samples, and this method is a destructive method. If the damage layer is not completely removed, it needs to be reworked to the grinding stage for secondary removal, which further consumes manpower and material resources. Summary of the invention

[0004] In order to solve the above problems, a method for non-destructive detection of the grinding damage layer of the grinding sheet is provided. The grinding damage layer of the grinding sheet can be directly tested by Raman to characterize the surface stress of the grinding sheet, thereby reflecting the size of the grinding damage layer of the grinding sheet. The detection method is a non-destructive test, and the detection results can, on the one hand, guide the improvement of the grinding process to reduce the introduction of grinding damage stress, and on the other hand, guide the subsequent polishing process to further remove the grinding damage layer of the grinding sheet.

[0005] According to one aspect of the present application, a method for non-destructive detection of a grinding damaged layer of a grinding sheet is provided, comprising the following steps:

[0006] (1) Extending 20-30 μm inward from the surface of the abrasive sheet to perform Raman testing on the surface of the abrasive sheet to obtain a stress distribution map of the surface of the abrasive sheet;

[0007] (2) The stress distribution diagram is divided into a first square area and a second square area, both of which have a side length of 100 μm. The first square area is an area where the absolute value of the stress value is greater than 35 MPa, and the second square area is an area where the absolute value of the stress value is less than or equal to 30 MPa. If the overall proportion of the stress distribution diagram in the first square area is greater than 3.5% and is irregularly scattered, it indicates that the grinding damage layer is not completely removed. If the overall proportion of the stress distribution diagram in the first square area is less than or equal to 3.5% and there is no obvious abnormal scattered distribution, it indicates that the grinding damage layer is easy to be completely removed.

[0008] The Raman detection method can be used to perform non-destructive testing on the grinding sheet, without having to wait until the grinding sheet is polished before testing, which can more intuitively reflect the quality of the grinding process; if the grinding damage layer is not completely removed in the test results, it can be determined whether to rework to the grinding stage or directly proceed to the next polishing process based on the state of the grinding damage layer of the grinding sheet. Since the polishing removal rate is slower than grinding, when the detection method detects that there is less residual grinding damage layer on the grinding sheet, the polishing process can be directly carried out to remove the excess grinding damage layer. When the grinding damage layer remains seriously, it cannot be completely removed by polishing alone, and the grinding process needs to be optimized to perform secondary grinding to reduce the grinding damage layer before polishing and removal. Therefore, this detection method can save the processing steps of the wafer and avoid problems such as thinning or uneven wafer thickness caused by secondary grinding and polishing.

[0009] Optionally, the calculation method of the stress distribution diagram is:

[0010] Coefficient determination: Before the Raman test, calculate the peak position shift and stress conversion coefficient of the polished sheet;

[0011] Test calculation: The peak value and peak offset of the wafer are obtained according to the Raman test, and the stress of the surface layer of the grinding sheet is calculated by the peak offset and the peak offset and stress conversion coefficient in step S1, so as to obtain the stress distribution diagram.

[0012] Optionally, the diameter of the grinding sheet is greater than 150 mm, preferably greater than 200 mm.

[0013] Optionally, the calculation steps of the peak position offset and the stress conversion coefficient are:

[0014] S1: Use a tester to test and calculate the interplanar spacing dx and interplanar spacing difference △d at different positions of the grinding sheet, and use Hooke's law or stress-strain formula to calculate the stress value at different positions;

[0015] S2: The peak position value of the polishing sheet is tested by Raman, and the peak position offset at different positions is calculated. The ratio of the peak position offset to the stress value is the peak position offset and stress conversion coefficient.

[0016] Optionally, the tester in S1 is selected from any one or more of an XRD diffractometer, a synchrotron radiation tester, a white light tester, a neutron diffractometer, a scanning electron microscope, and a transmission electron microscope.

[0017] When the substrate is tested by an XRD diffractometer, the interplanar spacing dx at different positions of the substrate is calculated using the Bragg diffraction formula.

[0018] In the above substrate surface stress test and substrate internal stress test, the peak value and peak offset in step S2 are obtained by fitting, and the fitting uses functions including Gaussian, Lorentz, GaussLor, AGauss, Aloren and AgaussLor.

[0019] Optionally, an equidistant focusing mode is used in the Raman test of step (1), wherein the equidistant focusing mode controls the distance between the Raman laser spot at each test point and the surface of the polishing sheet to be equal, and the peak position value and the peak position offset are obtained after fitting.

[0020] The automatic focusing function of the Raman tester can ensure that the laser spot hits the surface of the grinding sheet, so that the test is not affected by the surface undulations of the grinding sheet, thereby accurately testing the stress condition of the surface of the grinding sheet.

[0021] Optionally, the grinding sheet is a silicon carbide grinding sheet;

[0022] Preferably, the crystal form of the silicon carbide grinding sheet is one of 2H-SiC, 4H-SiC, 6H-SiC, 3C-SiC, and 15R-SiC.

[0023] According to another aspect of the present application, a silicon carbide grinding sheet is provided, wherein the silicon carbide grinding sheet is obtained by cutting and grinding a silicon carbide crystal, and the silicon carbide grinding sheet comprises a first main surface and a second main surface opposite to the first main surface;

[0024] The silicon carbide polishing sheet is divided into a first square region with a surface stress absolute value greater than 35 MPa and a length of 100 μm, and two square regions with a surface stress absolute value less than or equal to 30 MPa and a length of 100 μm, wherein the ratio of the number of the first square regions to the number of the second square regions is 1:(30-100), preferably 1:(31-100), and more preferably 1:(67-100);

[0025] The absolute value of the surface stress is the absolute value of the stress value detected in a region extending 20-30 μm inward from the first main surface or the second main surface.

[0026] The smaller the ratio of the number of the first square regions to the number of the second square regions, the larger the proportion of the second square regions, the smaller the proportion of the unremoved grinding damage layer contained in the silicon carbide grinding sheet, the better the quality of the silicon carbide grinding sheet, and the more conducive to subsequent polishing and processing. Preferably, the ratio of the number of the first square regions to the number of the second square regions is 1:100.

[0027] Due to the limitation of the shape of the silicon carbide grinding sheet, for the first square region and the second square region at the edge of the silicon carbide grinding sheet, there may be a situation where the area of ​​one first square region or the second square region is not satisfied. Therefore, the number of first square regions and second square regions may not be an integer. For example, the edge of the silicon carbide grinding sheet can only be divided into 50μm regions, but the absolute value of the surface stress in the region is less than or equal to 20MPa, then it is calculated as 0.25 second square regions according to the area ratio.

[0028] Optionally, at any plane parallel to the first main surface and / or the second main surface, S1 represents the average value of the absolute value of the surface stress in all the first square regions, S2 represents the average value of the absolute value of the surface stress in any of the first square regions, and 0.79≤S1 / S2≤1.35.

[0029] Optionally, the diameter of the silicon carbide grinding disc is greater than 150 mm, preferably greater than 200 mm.

[0030] Optionally, at any plane parallel to the first main surface and / or the second main surface, S3 represents an average value of the absolute values ​​of the surface stress in all the second square regions, S4 represents an average value of the absolute values ​​of the surface stress in any second square region, and 0.21≤S3 / S4≤1.50;

[0031] Preferably, 1.5≤S1 / S3≤10.

[0032] More preferably, 1.5≤S1 / S3≤9.9.

[0033] Multi-point stress detection is performed on the silicon carbide polishing sheet. The average value of the absolute value of the surface stress in the first square area or the second square area refers to the value obtained by dividing the sum of the absolute values ​​of the surface stress at all the detection points in the area by the number of detection points. The multi-point stress detection can be performed by selecting multiple points at different positions in the area for detection, or by performing a mapping test on the substrate.

[0034] The above-mentioned S1 / S2 ratio represents the difference between any first square region and the average value of all first square regions in the radial direction. The closer the ratio is to 1, the smaller the difference between the surface stresses of all first square regions in the radial direction is, that is, the smaller the regional difference of the grinding damage layer is, which means that the distribution of the grinding damage layer on the silicon carbide grinding sheet is more uniform.

[0035] Similarly, the above-mentioned S3 / S4 ratio represents the difference between any second square area and the average value of all second square areas in the radial direction. The closer the ratio is to 1, the smaller the difference between the surface stresses of all second square areas in the radial direction is, and the more uniform the stress distribution of the silicon carbide grinding sheet is, that is, the better the quality of the silicon carbide grinding sheet is; the S1 / S3 ratio represents the average radial internal stress ratio of the area with a grinding damage layer and the area without a grinding damage layer of the silicon carbide substrate in the radial direction, representing the difference between all the first square areas and the second square areas. The more grinding damage layers remain in the first square area, the greater the stress value of the first square area, and the greater the S1 / S3 ratio is, which means that the stress difference of the silicon carbide grinding sheet is greater, that is, the worse the quality is, and the more unfavorable it is for subsequent polishing and production processing.

[0036] Optionally, at any plane parallel to the first main surface and / or the second main surface, S max1 S is the maximum value of the surface stress in any of the first square regions. min1 Denote as the minimum value of the surface stress in any of the first square regions, △S1 = S max1 -S min1 , 10MPa≤△S1≤20MPa.

[0037] Preferably, 10.9MPa≤ΔS1≤20MPa.

[0038] Optionally, S max2 S is the maximum internal stress in any second square region. min2 It is denoted as the minimum surface stress in the second square region, △S2 = S max2 -S min2 , 10MPa≤△S2≤30MPa.

[0039] Preferably, 10.2MPa≤ΔS2≤30MPa

[0040] Since the silicon carbide grinding disc is subjected to tensile and compressive stress, the interplanar spacing d undergoes corresponding expansion and contraction changes. Therefore, when using Raman to test stress, the Raman peak intensity will appear to move to low frequency or high frequency. When the silicon carbide grinding disc is subjected to tensile stress, the Raman peak shifts to low frequency, and the obtained stress value is positive. When the silicon carbide grinding disc is subjected to compressive stress, the Raman peak shifts to high frequency, and the obtained stress value is negative. Therefore, the positive and negative before the stress value in this application represent the force direction of the silicon carbide grinding disc, and the absolute value of the value represents the magnitude of the stress. For example, when the surface stress in the first square area is -20MPa and the surface stress in the second square area is -10MPa, it means that the surface stresses in the first square area and the second square area are both compressive stresses, and the surface stress in the first square area is greater than the surface stress in the second square area.

[0041] The above S max1 , S min1 , S max2 and S min2 The meaning is the true value of the radial surface stress, which distinguishes between compressive stress and tensile stress in the radial direction. For example, at any plane parallel to the first main surface and / or the second main surface, the radial surface stress of the first square area is -10~5MPa, then the maximum value of the radial surface stress is 5MPa, and the minimum value of the radial surface stress is -10MPa. △S1 is 15MPa. △S1 and △S2 respectively represent the degree of change in the crystal plane spacing of the silicon carbide grinding sheet in the first square area and the second square area in the radial direction. The smaller the above △S1 and △S2 are, the smaller the change in the crystal plane spacing of the silicon carbide grinding sheet in the radial direction is, which means that the stress distribution of the silicon carbide grinding sheet is more uniform and the quality of the silicon carbide grinding sheet is better.

[0042] The above stress includes absolute stress and relative stress. Absolute stress can reflect the difference between the wafer and the perfect SiC crystal without defects, and is used to determine the stress level of the SiC wafer. However, since it is difficult to achieve perfect defect-free wafers with current technology, relative stress can be used to determine the relative stress distribution within the wafer surface.

[0043] For example, when the absolute stress of the chip is large and the relative stress is small, it means that the in-plane lattice distortion causes the stress to be large, but the stress distribution is uniform, the crystal quality is poor, and the stress quality in each area of ​​the chip is relatively uniform; if the absolute stress is small and the relative stress is large, the overall chip quality is good, but there are abnormal stress quality deviations in some areas.

[0044] The reference value of absolute stress in this application is the reference stress calculated based on the standard Raman peak position obtained based on the perfect lattice parameters of SiC, which is marked as 0; the relative stress is to take a reference value on the entire test plane, and the value of each test point is related to the reference value for numerical calculation to obtain the relative stress value of the test point. The reference value includes but is not limited to any one of the median, mean, mode or other statistical function calculation results of all stress values ​​on the entire test plane.

[0045] The beneficial effects of this application include but are not limited to:

[0046] 1. According to the detection method for the grinding damage layer of the grinding sheet of the present application, the grinding sheet is directly detected, which can not only intuitively characterize the degree of removal of the grinding damage layer by the grinding process, but also realize non-destructive detection. The appropriate post-processing procedure can be selected according to the residual degree of the grinding damage layer, saving detection time and avoiding waste of grinding sheets.

[0047] 2. According to the detection method for the grinding damage layer of the grinding sheet of the present application, the results obtained by the detection method can, on the one hand, guide the improvement of the grinding process to reduce the introduction of grinding damage stress, and on the other hand, guide the subsequent polishing process to further remove the grinding damage layer of the grinding sheet.

[0048] 3. According to the silicon carbide grinding sheet of the present application, the surface damage layer thereof is relatively low, which is conducive to the subsequent polishing and processing steps. Using it to prepare silicon carbide devices can improve the performance and yield of silicon carbide devices, facilitate mass production and processing, and save the processing cost of silicon carbide devices.

[0049] 4. According to the silicon carbide grinding sheet of the present application, the radial difference between the first square area and the second square area is small, and according to the ratio of the number and surface stress of all the first square areas and all the second square areas, it can be seen that the proportion of the first square areas is small, which proves that the quality of the silicon carbide grinding sheet is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0051] Figure 1 This is a flow chart for calculating the peak position offset and stress conversion coefficient involved in Example 1 of the present application.

[0052] Figure 2 This is a flow chart of the Raman stress test involved in Example 1 of the present application.

[0053] Figure 3Schematic diagram of the test of surface stress of the polished sheet in Raman equidistant focusing mode.

[0054] Figure 4 This is the Raman test image of the polished sheet.

[0055] Figure 5 Schematic diagram of the polished wafer after being etched with KOH solution. DETAILED DESCRIPTION

[0056] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0057] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0058] Example 1

[0059] This embodiment relates to a method for detecting a grinding damaged layer of a grinding sheet, comprising the following steps:

[0060] (1) Calculation of peak position shift and stress conversion coefficient

[0061] refer to Figure 1 First, a single crystal XRD diffractometer is used to test the silicon carbide wafer and the substrate is analyzed according to the reciprocal lattice space. The parameters of the standard silicon carbide wafer are calculated and compared with the standard parameters. Then, according to the Bragg diffraction equation: 2dsinθ=nλ, where d is the interplanar spacing, θ is the diffraction half-angle, n is the diffraction order, and λ is the wavelength, the θ and d of different silicon carbide wafers are tested. It can be seen that the tensile and compressive stress inside the wafer causes the interplanar spacing d to expand and contract accordingly. According to the different interplanar spacings d0 and d x , d x It is divided into d1 and d2, where d0 is the theoretical crystal plane spacing, d1 is the crystal plane spacing after tensile stress, and d1 is greater than d0, and d2 is the crystal plane spacing after compressive stress, and d2 is less than d0. The difference in crystal plane spacing △d at different positions is calculated, △d=d1-d0 or △d=d0-d2.

[0062] The actual peak position of the silicon carbide wafer is obtained according to the Raman test, and the peak position offset △v at different test points is calculated compared with the standard peak position; the stress value σ of the silicon carbide wafer at different test points is calculated in combination with Hooke's law or stress-strain formula, and the ratio of the peak position offset to the stress value at different test points is the peak position offset and the stress conversion coefficient μ, which ranges from -125 to -2500.

[0063] The calculation formula of Hooke's law is σ / S=E×(△d / d0), where S is the area where σ acts, which is a fixed value, E is the Young's modulus of the substrate, which is a fixed parameter of the substrate, △d is the difference in crystal plane spacing at different positions, d0 is the theoretical crystal plane spacing, and σ is the stress value that needs to be calculated.

[0064] The calculation formula of stress and strain is σ=E×△d, where E is the Young's modulus of the substrate, which is a fixed parameter of the substrate, △d is the difference in crystal plane spacing at different positions, and σ is the stress value to be calculated.

[0065] (2) Raman test of polished sheets

[0066] refer to Figure 2 First, set the Raman test points. You can perform single-point testing or Mapping scanning of the entire polishing sheet. Therefore, single-point testing is a sporadic coordinate point setting, and Mapping scanning is 10x10~50x50 and more points. You can choose the appropriate test method according to the properties of the substrate to determine the Raman test coordinate diagram of the polishing sheet.

[0067] The test results are then output, including but not limited to editable peak position, peak intensity data and Mapping.

[0068] The output data is then subjected to peak position fitting, where fitting functions include but are not limited to Gaussian, Lorentz, GaussLor, AGauss, Aloren and AGaussLor, to obtain precise peak position values ​​and peak position offsets, with the peak position accurate to more than one decimal place.

[0069] Finally, according to the peak shift and stress conversion coefficient μ calculated in (1) and the peak shift △v obtained in the Raman test, the stress value of silicon carbide is calculated as follows: σ(MPa)=μ×△v(cm -1 ).

[0070] Raman testing uses an equidistant focusing test method. The test principle is as follows: Figure 3 As shown, Figure 3 (b) Schematic diagram of the focus of the Raman laser on the damaged layer on the substrate surface. Figure 3 (a) is the test principle diagram. Under this test mode, the focal depth (d) of the Raman laser focused on the damaged layer on the surface of the polishing sheet at different test points remains unchanged.

[0071] By debugging the parameters of the Raman tester, the laser is focused on the surface of the polishing sheet using the automatic focusing function, so that the surface damage layer of the polishing sheet falls within the range of the laser spot, thereby achieving equal-spaced focusing tests at different test points of the polishing sheet, that is, the distance between the focusing plane and the substrate surface is always equal. This method is not affected by the bending and warping of the polishing sheet surface, so that the obtained Raman peak intensity is always maintained at the axial maximum value of the test point. According to the above-mentioned stress quantitative test method, the stress test image of the polishing sheet is obtained as follows: Figure 4 As shown, Figure 4 (a) is a schematic diagram showing that the damaged layer of the grinding sheet is not completely removed. Figure 4 (b) is a schematic diagram showing the complete removal of the damaged layer by the grinding wheel.

[0072] The polished wafer obtained after the same grinding process and polishing was etched with hot KOH solution. The results are as follows Figure 5 As shown, under an optical microscope, Figure 5 (a) There are a large number of dense teardrop-shaped corrosion pits, which is a schematic diagram of the incomplete removal of the grinding damage layer of the grinding sheet. Figure 5 (b) Only dislocation corrosion pits are visible, and other areas are flat and smooth, which is a schematic diagram of the complete removal of the grinding damage layer by the grinding sheet.

[0073] Example 2

[0074] This embodiment relates to a grinding process for a silicon carbide wafer, in which the cut silicon carbide wafer is placed in a grinder, and a mixed grinding material of nanofluid, abrasive and grinding liquid is added to grind the wafer, and the grinding process is to use a grinding pad with diamond particles of W5 for grinding. The specific grinding process is as follows:

[0075] 1. First, prepare nanofluids, select dispersant-modified SiO2, Si, and SiC as nanopowders, the concentration of the nanopowders is 1.5%-3.5%, and the particle size of the nanopowders is 10-1000nm; use heat-conducting oil or a mixed solution of ethylene glycol and water as the nanofluid carrier liquid, add 10%-11% of the dispersant and 3%-5% of the modifier, use an ultrasonic stirrer to ultrasonically stir the above-mentioned liquid until the nanopowders are evenly dispersed in the carrier liquid, and finally use diluted HCl and NaOH as pH regulators to adjust the pH to 7.5-9 to obtain nanofluids.

[0076] In the preparation of nanofluids, the above "%" refers to the weight percentage of the added substance in the nanofluid carrier liquid.

[0077] Then, the grinding material is prepared, and the grinding material uses nanofluid as the grinding material carrier. 20%-30% of boron carbide and diamond powder grinding materials are added to the nanofluid, wherein the weight ratio of boron carbide to diamond powder is 1.5-4:1, the particle size of boron carbide is 5-6μm, and the particle size of diamond is 6-8μm, and then 1-3% of suspending agent is added, and dispersing agent is added again, so that the volume ratio of suspending agent to dispersing agent in the whole system is 1:20-25, and the grinding material is obtained.

[0078] In the preparation of the abrasive material, the above "%" refers to the weight percentage of the added substance in the nanofluid.

[0079] The above-mentioned dispersants include but are not limited to glycerol, polyethylene glycol, sodium hexametaphosphate, sodium pyrophosphate, and sodium orthophosphate; the modifiers include but are not limited to soft sodium alkylbenzene sulfonate and taurate; and the suspending agents include but are not limited to polyvinyl alcohol and BYK.

[0080] 2. Then, the cut SiC wafer is roughly ground to remove the surface marks of the cut wafer. The diamond powder particle size is W7 and the pressure is 30g / cm 2 The speed ratio of the inner and outer ring gears is 1:2 for rough grinding, and the rough grinding time is 1h.

[0081] 3. After the rough grinding, the middle grinding is carried out to remove the micro cracks under the cutting line marks and thin the cutting damage layer. The process used is to select diamond powder as W5 and adjust the pressure to 70g / cm 2 The speed ratio of the inner and outer gear rings is 1:2 for mid-section grinding, and the grinding time is 1h.

[0082] 4. Finally, the sample is finely ground to remove the damaged layer introduced by the previous grinding as much as possible, so that the grinding damaged layer can be removed as much as possible for subsequent polishing. The diamond powder particle size is W3.5 and the pressure is 50g / cm 2 The speed ratio of the inner and outer gear rings is 1:4 for fine grinding, and the fine grinding time is 3 hours to obtain the silicon carbide grinding sheet.

[0083] The above-mentioned grinding process is used to prepare silicon carbide grinding sheets 1#-8#, wherein steps 2-4 adopt the above-mentioned process, and the difference of step 1 is as follows:

[0084] Silicon carbide grinding disc 1#

[0085] Firstly, a nanofluid is prepared, SiC surface-modified with sodium hexametaphosphate is selected as a nano powder, the concentration of the nano powder is 3.5%, and the particle size of the nano powder is 300 nm; a mixed solution of ethylene glycol and water is used as a nano fluid grinding liquid carrier, the ratio of ethylene glycol to water is 3:5, in addition, 10% of glycerol and 0.1% of sodium hexametaphosphate are added as a dispersant, and 5% of soft alkylbenzene sodium sulfonate is added as a modifier, an ultrasonic stirrer is used to ultrasonically stir the above-mentioned liquid until the nano powder is evenly dispersed in the carrier liquid, and finally diluted HCl and NaOH are used as pH regulators to adjust the pH to 8 to obtain a nano fluid.

[0086] Then, the abrasive is prepared, and the abrasive uses nanofluid as the abrasive carrier. 25% of abrasives of boron carbide and diamond powder are added to the nanofluid, wherein the weight ratio of boron carbide to diamond powder is 3:1, the particle size of boron carbide is 6 μm, and the particle size of diamond is 7 μm. Then, 1.4% BYK is added as a suspending agent, and glycerol is added again as a dispersing agent, so that the volume ratio of the suspending agent to the dispersing agent in the whole system is 1:25, and the abrasive material 1# is obtained. The abrasive material 1# is used to grind the cut wafer in steps 2-4, and the silicon carbide grinding sheet 1# is obtained.

[0087] Silicon carbide grinding disc 2#

[0088] Firstly, a nanofluid is prepared, SiO2 surface-modified with sodium pyrophosphate is selected as a nanopowder, the concentration of the nanopowder is 3.5%, and the particle size of the nanopowder is 10 nm; a mixed solution of ethylene glycol and water is used as a nanofluid grinding liquid carrier, and the ratio of ethylene glycol to water is 3:5. In addition, 10% glycerol and 0.1% sodium pyrophosphate are added as dispersants, and 3% soft alkylbenzene sodium sulfonate is added as a modifier. An ultrasonic stirrer is used to ultrasonically stir the above-mentioned liquid until the nanopowder is evenly dispersed in the carrier liquid. Finally, diluted HCl and NaOH are used as pH regulators to adjust the pH to 7.5 to obtain a nanofluid.

[0089] Then, the abrasive is prepared, and the abrasive uses nanofluid as the abrasive carrier. 20% of abrasives of boron carbide and diamond powder are added to the nanofluid, wherein the weight ratio of boron carbide to diamond powder is 4:1, the particle size of boron carbide is 5 μm, and the particle size of diamond is 8 μm. Then, 3% BYK is added as a suspending agent, and glycerol is added again as a dispersing agent, so that the volume ratio of the suspending agent to the dispersing agent in the whole system is 1:20, and the abrasive material 2# is obtained. The above-mentioned abrasive material 1# is used to grind the cut wafer in steps 2-4, and the silicon carbide grinding sheet 2# is obtained.

[0090] Silicon carbide grinding disc 3#

[0091] Firstly, a nanofluid is prepared, Si surface-modified with sodium orthophosphate is selected as a nanopowder, the concentration of the nanopowder is 1.5%, and the particle size of the nanopowder is 1000 nm; a mixed solution of ethylene glycol and water is used as a nanofluid grinding liquid carrier, and the ratio of ethylene glycol to water is 3:5. In addition, 10% glycerol and 1% sodium orthophosphate are added as dispersants, and 5% taurate is added as a modifier. An ultrasonic stirrer is used to ultrasonically stir the above-mentioned liquid until the nanopowder is evenly dispersed in the carrier liquid. Finally, diluted HCl and NaOH are used as pH regulators to adjust the pH to 9 to obtain a nanofluid.

[0092] Then, the abrasive is prepared, and the abrasive uses nanofluid as the abrasive carrier. 30% of abrasives of boron carbide and diamond powder are added to the nanofluid, wherein the weight ratio of boron carbide to diamond powder is 2:1, the particle size of boron carbide is 6 μm, and the particle size of diamond is 6 μm. Then, 1% BYK is added as a suspending agent, and glycerol is added again as a dispersing agent, so that the volume ratio of the suspending agent to the dispersing agent in the whole system is 1:25, and the abrasive material 3# is obtained. The above-mentioned abrasive material 1# is used to grind the cut wafer in steps 2-4, and the silicon carbide grinding sheet 3# is obtained.

[0093] Silicon carbide grinding disc 4#

[0094] The difference between this silicon carbide grinding sheet 4# and silicon carbide grinding sheet 1# is that SiO2 surface-modified with sodium pyrophosphate and Si surface-modified with sodium orthophosphate are used as nanopowders, with concentrations of 2% and 1% respectively, and the remaining materials and grinding steps are the same as those of silicon carbide grinding sheet 1#, thus obtaining silicon carbide grinding sheet 4#.

[0095] Silicon carbide grinding wheel 5#

[0096] The difference between the silicon carbide grinding sheet 5# and the silicon carbide grinding sheet 1# is that heat transfer oil is used as the nanofluid carrier, and the other materials and grinding steps are the same as those of the silicon carbide grinding sheet 1#, so as to obtain the silicon carbide grinding sheet 5#.

[0097] Silicon carbide grinding wheel 6#

[0098] The difference between the silicon carbide grinding sheet 6# and the silicon carbide grinding sheet 1# is that the particle size of the nano powder is 800nm, and the other materials and grinding steps are the same as those of the silicon carbide grinding sheet 1#, so as to obtain the silicon carbide grinding sheet 6#.

[0099] Comparison of Silicon Carbide Grinding Sheet D1#

[0100] The difference between the comparative silicon carbide grinding sheet D1# and the silicon carbide grinding sheet 1# is that the concentration of the nano powder used is 5%, and the remaining materials and grinding steps are the same as those of the silicon carbide grinding sheet 1#, thus obtaining the comparative silicon carbide grinding sheet D1#.

[0101] Comparison of Silicon Carbide Grinding Sheet D2#

[0102] The difference between the comparative silicon carbide grinding sheet D2# and the silicon carbide grinding sheet 1# is that the particle size of boron carbide is 10μm, the particle size of diamond is 3μm, and the remaining materials and grinding steps are the same as those of the silicon carbide grinding sheet 1#, thus obtaining the comparative silicon carbide grinding sheet D2#.

[0103] The above silicon carbide grinding sheet was characterized by the detection method of Example 1, and the data is shown in Table 1 below.

[0104] Table 1

[0105]

[0106] The performance parameters of the grinding sheets in Table 1 are all calculated by relative stress values, and the data in Table 1 are only the grinding sheets prepared by combining some processing parameters in Example 2. When the other processing parameters in the grinding process of Example 2 are used to prepare the grinding, and the absolute stress is used to characterize the performance parameters of the grinding sheets in Table 1, the grinding sheets can still meet the requirements that the ratio of the number of the first square areas to the number of the second square areas is 1: (30-100); 0.79≤S1 / S2≤1.35; 0.21≤S3 / S4≤1.50; 1.5≤S1 / S3≤10; 10MPa≤△S1≤20MPa; 10MPa≤△S2≤30MPa.

[0107] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for non-destructive testing of abrasive sheet grinding damage layer, It is characterized in that The steps include: (1) Extending 20-30 μm inward from the surface of the abrasive sheet to perform Raman testing on the surface of the abrasive sheet to obtain a stress distribution map of the surface of the abrasive sheet; (2) The stress distribution diagram is divided into a first square region and a second square region, both of which have a side length of 100 μm. The first square region is a region where the absolute value of the stress value is greater than 35 MPa, and the second square region is a region where the stress value is less than or equal to 30 MPa. If the overall proportion of the stress distribution diagram in the first square region is greater than 3.5% and is irregularly scattered, it indicates that the grinding damage layer is not completely removed. If the overall proportion of the stress distribution diagram in the first square region is less than or equal to 3.5% and there is no obvious abnormal scattered distribution, it indicates that the grinding damage layer is easy to be completely removed.

2. The method according to claim 2, It is characterized in that The calculation method of the stress distribution diagram is: Coefficient determination: Before the Raman test, calculate the peak position shift and stress conversion coefficient of the polished sheet; Test calculation: obtaining the peak value and peak offset of the wafer according to the Raman test, calculating the stress of the surface layer of the polishing sheet by the peak offset and the peak offset and stress conversion coefficient in step S1, that is, obtaining the stress distribution diagram; and / or The diameter of the grinding sheet is greater than 150 mm.

3. The method according to claim 2, It is characterized in that The calculation steps of the peak position offset and the stress conversion coefficient are as follows: S1: Use a tester to test and calculate the interplanar spacing dx and interplanar spacing difference △d at different positions of the grinding sheet, and use Hooke's law or stress-strain formula to calculate the stress value at different positions; S2: The peak position value of the polishing sheet is tested by Raman, and the peak position offset at different positions is calculated. The ratio of the peak position offset to the stress value is the peak position offset and stress conversion coefficient.

4. The method according to claim 3, It is characterized in that The tester in S1 is selected from any one or more of an XRD diffractometer, a synchrotron radiation tester, a white light tester, a neutron diffractometer, a scanning electron microscope, and a transmission electron microscope.

5. The method according to claim 1, It is characterized in that In the Raman test of step (1), an equidistant focusing mode is used, wherein the equidistant focusing mode controls the distance between the Raman laser spot at each test point and the surface of the polishing sheet to be equal, and the peak position value and the peak position offset are obtained after fitting.

6. A silicon carbide grinding sheet, It is characterized in that The silicon carbide grinding sheet is obtained by cutting and grinding silicon carbide crystals, and the silicon carbide grinding sheet includes a first main surface and a second main surface opposite to the first main surface; Dividing the silicon carbide polishing sheet into a first square region with a surface stress absolute value greater than 35 MPa and a length of 100 μm, and a second square region with a surface stress absolute value less than or equal to 30 MPa and a length of 100 μm, wherein the ratio of the number of the first square region to the number of the second square region is 1:(30-100); The absolute value of the surface stress is the absolute value of the stress value detected in a region extending 20-30 μm inward from the first main surface or the second main surface.

7. The silicon carbide polishing sheet according to claim 6, It is characterized in that At any plane parallel to the first main surface and / or the second main surface, S1 represents the average value of the absolute values ​​of the surface stress in all the first square regions, S2 represents the average value of the absolute values ​​of the surface stress in any of the first square regions, and 0.79≤S1 / S2≤1.35; The diameter of the silicon carbide grinding sheet is greater than 150 mm.

8. The silicon carbide polishing sheet according to claim 7, It is characterized in that At any plane parallel to the first main surface and / or the second main surface, S3 represents the average value of the absolute values ​​of the surface stress in all the second square regions, S4 represents the average value of the absolute values ​​of the surface stress in any second square region, and 0.21≤S3 / S4≤1.50; Preferably, 1.5≤S1 / S3≤10.

9. The silicon carbide polishing sheet according to claim 6, It is characterized in that At any plane parallel to the first main surface and / or the second main surface, S max1 S is the maximum value of the surface stress in any of the first square regions, min1 Denote as the minimum value of the surface stress in any of the first square regions, △S1 = S max1 -S min1 , 10MPa≤△S1≤20MPa.

10. The silicon carbide polishing sheet according to claim 9, It is characterized in that S max2 S is the maximum surface stress in any second square region. min2 Denote as the minimum surface stress in any second square region, △S2 = S max2 -S min2 , 10MPa≤△S2≤30MPa.

Citation Information

Patent Citations

  • Test method for residual stress of subsurface of grinding wafer

    CN105067168A

  • Silicon carbide substrate and method for producing silicon carbide substrate

    CN114651091A

  • Method for evaluating compound semiconductor substrate, method for producing the same, and the compound semiconductor substrate

    JP2009057233A

  • Sample analyzing device and sample analysis program

    JP2017062263A

  • Non-destructive analysis for TSD and TED defect of silicon carbide wafers

    KR102381348B1